Rethinking patient involvement in healthcare priority setting - Sandman, Lars (Bioethics, 2020)
With healthcare systems under pressure from scarcity of resources and ever-increasing demand for services, difficult priority setting choices need to be made. At the same time, increased attention to patient involvement in a wide range of settings has given rise to the idea that those who are eventually affected by priority setting decisions should have a say in those decisions. In this paper, we investigate arguments for the inclusion of patient representatives in priority setting bodies at the policy level. We find that the standard justifications for patient representation, such as to achieve patient-relevant decisions, empowerment of patients, securing legitimacy of decisions, and the analogy with democracy, all fall short of supporting patient representation in this context. We conclude by briefly outlining an alternative proposal for patient participation that involves patient consultants.